CommunicAids Aids Communication: Newsletter Teaches Oregon Extension Workers to Be Better Communicators - Joyce Patterson (Journal of Applied Communications, 1988)
The Oregon State University Agricultural Communications faculty prepares a monthly newsletter with information about communication methods and materials. In 1987 it evaluated the newsletter to determine effectiveness as a way to teach Extension workers to be better communicators. Following random selection procedures, a written questionnaire was sent to every third person who receives the newsletter. Statistically, the reponse was 100%. The one person who did not respond was no longer on the staff. Ninety percent of the respondents replied that the newsletter is useful and the length of the articles about right. Forty-nine percent use the annual index to look up previous articles. Respondents made suggestions, which the writers have followed, such as punching the newsletter for three-ring binders and printing on white rather than on colored paper. Respondents also suggested topics for future articles, upon which the writers are acting.